Gender Influence on the Perception of Celebrity Endorsement - Lazăr, Laura (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
Celebrity endorsement is a common instrument in marketing. Celebrities are also present in commercials, and this phenomenon is nowadays a trend. This kind of publicity has a high potential since customers are pulled into the VIPs. They are overpowered by their regular daily existence, so they need standards and good examples. This is the motivation for using superstar brand envoys in advertisings as an excellent promoting technique of brands and products. In the period of data and promotions, the tributes can get the consumers’ consideration in publicizing and to expand how the promoted item is being perceived. This is because of their fame, glamour, elegance and charisma. For this reason, the marketers are looking for popular, famous, beautiful, positive testimonials to drive a company’s image and its products. The celebrity brand ambassadors thus play a significant role in a brand’s advertisement and reputation, but also in the consumers’ lives. The stars’ everyday lives, their conduct, the products they use, affect the attitude of the customers of life and the decision to purchase. The purpose of this paper is to determine if celebrity endorsement works for all the consumers or the perception of this trend is different according to the gender of the people. Two groups of customers were asked about celebrity endorsement whether their appearance in ads affects their decision and the desire to purchase a product or not. Recent results have shown that there are still differences between the two categories of customers, men and women, in the perception of celebrity endorsement. All of them think advertising is important, and sometimes they change their choices according to a product’s advertisement. The difference is that women appear to believe more in the endorsements of celebrity brands and their impact effect on the product being marketed than men, who are more pragmatic and reticent about this trend.